Biosensors for non invasive monitoring of physiological biomarkers related to fitness, sports and wellbeing - Tervo, P.; Ohtonen, E.; Pääkkönen, S.; Mäki, M.; Sonny, S.; Mahosenaho, M.; Virtanen, V.; Sesay, A. M. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Biosensors are analytical devices that combine a biological component, such as an enzyme or an antibody to a physicochemical transducer to detect an analyte of interest (1). In the field of sport sciences, monitoring the status of athletic fitness and sporting performance can be evaluated by applying biosensor technology, as they offer rapid and sensitive detection of relevant biological physiological markers from biological samples. The use of saliva and sweat as noninvasive biological samples can offer an easy and stress-free way for monitoring metabolic, immunological, nutritional, and stress biomarkers that are highly correlated with their concentration levels in blood (2). Current developments in biosensing technology and the availability of new novel materials, flexible electronics and wireless mobile technology; should enable a new generation of devices that will operate on the cutting edge sports science research in understanding fitness and athletic performance.